Physical activity and sports sciences between European Research Council and academic disciplines in Italy - Raiola, Gaetano; D’Elia, Francesca; Altavilla, Gaetano (Journal of Human Sport and Exercise, 2018)
Also in Italy, as well as to be in all others states European Union, the academic disciplines in university system have to change to conform to the 3 areas: SH Social Sciences and Humanities, PE Physical Sciences and Engineering, LS (Life Sciences), 25 panel and 333 sub panel of European Research Council Panel Structure 2018. Nowadays, it is compulsory to have the same language within the European Union and its European Research Council Executive Agency (ERCEA). This change concerns the funding of research and the recruitment of professors; currently in Italy they follow two different procedures and the reform aims to pursue the unique way. Physical activity and sports sciences are in two different scientific areas: the human and social sciences and the life sciences. The problem is therefore to choose a single scientific area or to stay in two areas, to define the declaration of the academic discipline with the protection of the professors rights and the relationship with the ERC Area. The academic disciplines of Physical activity and Sport sciences field could be made by the following descriptors: Health, ageing - Social aspects of learning, curriculum studies, educational policies - Science and technology studies - Cognitive basis of human development and education, developmental disorders; comparative cognition - Personality and social cognition – Emotion - Clinical and health psychology – Neuropsychology - Attention, perception, action, consciousness - Learning, memory - Cognition in ageing - Reasoning, decision-making – Intelligence - Language learning and processing - Theoretical linguistics - computational linguistics - Comparative physiology and pathophysiology - Fundamental mechanisms underlying ageing - Sensation and perception - Neural bases of cognitive processes - Other medical technologies for diagnosis and monitoring of diseases - Epidemiology and public health - Environmental health, occupational medicine - Health services, health care research, medical ethics. In Italy its declaratory could be simplified: “Theories and methods of physical education, training, health and well-being” in Life sciences area with the exception for some professors to be structured in human and social sciences for educational profile.